Hyperbaric Oxygen Therapy in Bitches with Dioctophymosis - Caye, Pâmela; Gasparotto, Jean Carlos; Nascimento Antunes, Bernardo; Debeluck Plentz, Isadora; Amaral Hasan, Jamile; Curvello de Mendonça Müller, Daniel; Machado Silva, Marco Augusto; Veloso Brun, Maurício (Acta Scientiae Veterinariae, 2024)
Background: Hyperbaric oxygen therapy (HBOT) is a therapeutic modality in which pure and pressurized oxygen is delivered to the patient, causing tissue hyperoxygenation and consequent improvements in the inflammatory state, immune defense capacity, and healing. It is performed in pressurized chambers with oxygen, specific for the therapy. Dioctophyme renale, a nematode, is a parasite in mammals that causes severe, chronic, and progressive kidney damage. It is usually diagnosed through abdominal ultrasonography. Most cases are asymptomatic, and the treatment of choice is surgery. This report concerns 2 cases of conditioning with HBOT before laparoscopic right nephrectomy. Cases: Two adult bitches, both of mixed breed, parasitized naturally by Dioctophyme renale in the right kidney, and were treated at the Veterinary Hospital. The bitch in case 1 had no clinical signs of the disease, whereas the bitch in case 2 had hematuria for 3 years. Parasite eggs were not found in the urine of either dog. Both dogs underwent 2 presurgical HBOT sessions, 24 h apart, at a pressure of 2 absolute total atmospheres for 30 min. Immediately after the 2nd session, general anesthesia was induced, and the dogs underwent laparoscopic right nephrectomy in the left lateral decubitus position, and surgical access was through 3 portals in the right flank. Hemostasis was achieved with titanium clips in case 1 and with bipolar forceps with impedance control in case 2. The parasitized kidneys were placed in a tissue extractor bag and removed from de cavity, and the surgical wound was sutured in 3 layers. Three male parasites were removed from the kidney in case 1 and one male parasite from that in case 2. Neither patient had free parasites in the abdominal cavity. No intraoperative or postoperative complications occurred. Hematological examinations revealed improvement in the red blood cell count and a decrease in the serum fibrinogen level in case 1 and a decrease in the red series and an increase in the serum fibrinogen level in case 2. Both patients had decreased total numbers of leukocytes and platelets. Discussion: Studdies have shown that presurgical hyperbaric conditioning improves renal and hepatic response to ischemia-reperfusion disorders, such as those that may occur during laparoscopies. Such disorders result from the creation of a pneumoperitoneum during the procedure, which increases intra-abdominal pressure. These tissues may receive cytoprotection mediated by the expression of heme-oxygenase 1, an anti-inflammatory substance induced by HBOT. Although the red series was reduced in case 2, it remained within the harmless reference range for the species. The increase in the red series in case 1 demonstrates the potential benefit of HBOT, inasmuch as many animals with D. renale have anemia. Because dioctophymosis leads to chronic kidney damage, a mild inflammatory response is expected. Thus, therapies that reduce systemic inflammation, such as HBOT, are beneficial to patients. Preoperative oxygenation is also recommended in animals undergoing long procedures. The results obtained in these 2 cases were different, but the benefits already proven by the consulted literature indicate that hyperbaric therapy can be advantageous in animals undergoing surgery. HBOT proved to be beneficial in the preoperative conditioning of 2 bitches with Dioctophyme renale, and both animals tolerated very well the therapy. Keywords: hyperbaric oxygen therapy, dioctophymosis, parasitology, giant kidney worm.